IMPLEMENTASI PERATURAN MENTERI AGRARIA DAN TATA RUANG/KEPALA BPN NOMOR 6 TAHUN 2018 TENTANG PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DALAM UPAYA DALAM UPAYA MENCEGAH SENGKETA PERTANAHAN DI KABUPATEN ENDE - Sepal, Yohan Yoan; Aloysius, Sukardan; Hedewata, Agus (Petitum Law Journal, 2023)
Abstract: Abstracts The main problem with PTSL that occurs in Ende Regency is the difficulty of finding village/sub-district areas that are willing to have their land plots legalized. This happens because the majority of Mosalaki refuse to make their area a PTSL object, even though the local village/sub-district government agrees. This research is a type of empirical legal research in which the data is obtained directly from the field or research location. This research uses interview guidelines from several data sources and is analyzed descriptively. The results of this research show that indigenous communities have the existence of legal unity, unity of authority and territorial unity which is recognized by the regional government. The existence of the authority of traditional leaders makes it a challenge for most villages in Ende Regency to still have Mosalaki. Mosalaki, as a symbol of the existence of traditional communities, is responsible for carrying out traditional authority over rituals and control of traditional lands. Therefore, in implementing PTSL, the Ende Regency Land Office is obliged to consult with Mosalaki to obtain support and approval for the area to be designated as a PTSL location. The difficulty in obtaining Mosalaki's approval is a major inhibiting factor in PTSL activities from village to village. Concerns about the release of land ownership from members of the traditional community to other people as well as the disorderly methods of members of the traditional community regarding customary provisions after land certification became Mosalaki's basis for rejecting the location of PTSL in his territory.